Segredos de Um defeito de cor: fabulações narradas por uma griotte - Vieira, Náira Araújo (2024)
The intention behind this paper is to investigate the Ana Maria Gonçalves novel, Um defeito de cor (2022), from the perspective of a narrator-griotte. In order to achieve the general goal, the fictionalization of the characters is analyzed in the light of the conception of the critical fabulation; the narrative tools used by the narrator-griotte to fable Kehinde and the relation to other characters is learned; the research reflects over the literary strategies of the novel, and over the methods of resistence of the black characters during the period of slavery through the concepts of “secrecy” and “Browning”; the image of Kehinde is analized starting from the conection between spiral time and body-canvas. The research’s problematic comes from the critical fabulation of fictional breeches of History, highlighting not only the brazilian structure of slavery, but also the lives that were erased and strategies of resistence. The hypothesis that guided the study was: the narrator-griotte surpasses the dominant linear thinking of History and possibilitates a narration of the slaver period that reconstructs memories, and reclaims images that were once atributed to customs, cultures, languages, african times, used as tools of survival, of encounters, and of the forming of quilombos. The hypothesis was tested with the theorical support of black authors, such as Saidiya Hartman (2020), Conceição Evaristo (2020), Dénètem Touam Bona (2020), and Leda Maria Martins (2021). The argumentation is developed throughout three chapters: in the first one, not only considerations about the novel are presented, but it also questions History, and the connection between the protagonist and Luíza Mahin; it also analyzes the narrator’s power to create black characters and to recreate the existence and memory of the black colectivity from the concept of critical fabulation. In the second chapter, the concepts of “secrecy” and “browning” are presented to analyze the narrative structure of the novel and to seize the ancestral and spiritual relationship that provided the reencounter between the characters Agontimé and Kehinde. In the third chapter, the construction of the body-canvas of the book and of Kehinde is analyzed from the concepts of “spiral time” and “body-canvas”, which build material and mental images awakened by it’s vision. The narration of Kehinde, by the utilization of theorical-critical decolonized conceptions, potentializes the voice of a african woman, a griotte, and recreates the memory of black colectivity and reframes it’s image